@GURUKUMRD: the Greatest Way to Learn English Vocabulary - Santiana, Santiana; Hadiningrum , Akhiria; Andriani, Agis (Yayasan Corolla Education Centre, 2023)
Social media has impacted teenagers all around the world to be aware of the benefits of mobile phones for acquiring information, entertainment, and edutainment during the previous decade. 21st-century learners often favour Instagram, which is a well-liked social networking platform. The researchers seek to examine how undergraduate students in Indonesia use @gurukumrd Instagram to learn English vocabulary. This study presents a case study of how students learn about learning activities through the @gurukumrd account. Braun and Clarke (2006) obtained data through semi-structured interviews as an instrument and evaluated it qualitatively using thematic analysis. The participants were students in the sixth and eighth semesters of one university in West Java, Indonesia. The findings of this study are; Students acquire knowledge independently, select vocabulary and pronunciation resources, learn in a short period of time through @gurukumrd, memorize the vocabulary, imitate the pronunciation of the vocabulary, and engage in daily dialogue using the vocabulary. This finding indicates that students learning vocabulary through the @gurukumrd Instagram account valued time flexibility, effectiveness, independent learning, and interest-based learning.